Asynchronous Interactions In New Media Art - Bulduk, Bülent (Atlas Journal, 2024)
With the 20th century, art and art practices began to take shape through an intellectual process. The changing language of the new world has changed both the perception of the artist and the means of art. The artist was not left out of these new technological or industrial processes. On the contrary, he knows how to use new tools and materials as an artistic language. In this context, New Media as a new medium has opened up different areas of experience for both the artist and the viewer. It has enabled practices of interaction, asynchronicity and synchronicity beyond traditional narratives. While constructing their new media practices, artists have created a fluid environment that does not exclude the audience but keeps them within the work. With the use of digital technology, television, telephone, telegraph and telecommunications, which are valuable on their own, have turned into a hybrid tool in the same environment as multi-media. Artists have been influenced by these hybrid tools and transformed these tools into an art form in a unique way. In this context, this research study will focus on the language of New Media tools that allow interaction and asynchrony in terms of artistic practices.